The Role of RUPBASAN Wonogiri in the Auction Process State Booty to Realize Non-tax revenue - Muhammad Rafi Hafizuddin Putra; Siti Nurlaela; Anita Wijayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The Wonogiri State Confiscated Goods Storage House (Rupbasan) is one of the government agencies authorized to store and manage state confiscated goods and state confiscation until the auction process is carried out. This study aims to determine the role of the Wonogiri Rupbasan in the auction process for state booty, the obstacles that arise in the Wonogiri Rupbasan in the state booty auction process and efforts to resolve the obstacles in realizing Non-Tax State Revenue. This study uses empirical legal research methods with data collection techniques from interviews and interviews. The results of this study are related to the role of the Wonogiri Rupbasan in the auction process for stolen goods from the state, both from before the auction process until the auction process is carried out. Before being auctioned there is an acceptance process, consisting of research, judgment, documentation, second registration, third management consisting of storage, security, maintenance, rescue, fourth use of Basan and Baran, fifth transfer, finally reporting. For the auction process, the Wonogiri Rupbasan uses an auction system that is displayed to the Ministry of Finance's State Assets and Auction Service Office in carrying out the auction. The Wonogiri Rupbasan prepares state-appropriated goods to be auctioned based on a court decision, puts up and submits a list of auctions, announces them to the public, records the auction winners given by the KPKNL, processes the taking of the auctioned items that have been won. Handling after the auction process is spending and cleaning. In the auction process there are several obstacles, both from internal Rupbasan and external constraints and there are also general obstacles outside the auction process which impact on the quality of the loot to be auctioned as well as efforts to resolve obstacles in the auction process for state loot. Suggestions due to the suboptimal role of the mandate and function of Rupbasan both in the bidding process and managing Basan and Baran, studies, policies and government decisions are needed in making regulations strengthening the sovereignty of Rupbasan. Improving coordination between the Wonogiri Rupbasan and related agencies in implementing the auction process for state loot so that it can run optimally and professionally